ABD-Derived Protein Blockers of Human IL-17 Receptor A as Non-IgG Alternatives for Modulation of IL-17-Dependent Pro-Inflammatory Axis - Hlavničková, Marie; Kuchař, Milan; Osička, Radim; Vaňková, Lucie; Petroková, Hana; Malý, Michal; Černý, Jiří; Arenberger, Petr; Malý, Petr (International journal of molecular sciences, 2018)
Interleukin 17 (IL-17) and its cognate receptor A (IL-17RA) play a crucial role in Th17 cells-mediated pro-inflammatory pathway and pathogenesis of several autoimmune disorders including psoriasis. IL-17 is mainly produced by activated Th-17 helper cells upon stimulation by IL-23 and, via binding to its receptors, mediates IL-17-driven cell signaling in keratinocytes. Hyper-proliferation of keratinocytes belongs to major clinical manifestations in psoriasis. To modulate IL-17-mediated inflammatory cascade, we generated a unique collection of IL-17RA-targeting protein binders that prevent from binding of human IL-17A cytokine to its cell-surface receptor. To this goal, we used a highly complex combinatorial library derived from scaffold of albumin-binding domain (ABD) of streptococcal protein G, and ribosome display selection, to yield a collection of ABD-derived high-affinity ligands of human IL-17RA, called ARS binders. From 67 analyzed ABD variants, 7 different sequence families were identified. Representatives of these groups competed with human IL-17A for binding to recombinant IL-17RA receptor as well as to IL-17RA-Immunoglobulin G chimera, as tested in enzyme-linked immunosorbent assay (ELISA). Five ARS variants bound to IL-17RA-expressing THP-1 cells and blocked binding of human IL-17 cytokine to the cell surface, as tested by flow cytometry. Three variants exhibited high-affinity binding with a nanomolar Kd value to human keratinocyte HaCaT cells, as measured using Ligand Tracer Green Line. Upon IL-17-stimulated activation, ARS variants inhibited secretion of Gro-α (CXCL1) by normal human skin fibroblasts in vitro. Thus, we identified a novel class of inhibitory ligands that might serve as immunosuppressive IL-17RA-targeted non-IgG protein antagonists.
Keywords: Protein Binding; Protein Stability; Recombinant Proteins; Cell Line; Inflammation; interakční proteinové domény a motivy; stabilita proteinů; Bacterial Proteins; Interleukin-17; mediátory zánětu; cytokiny; Receptors, Interleukin-17; molekulární modely; zánět; Carrier Proteins; rekombinantní proteiny; Models, Molecular; vazba proteinů; Protein Interaction Domains and Motifs; lidé; konformace proteinů; interleukin-17; Humans; bakteriální proteiny; buněčné linie; receptory interleukinu-17; Cytokines; Inflammation Mediators; Protein Conformation; transportní proteiny